Research Progress of PD-1/PD-L1 Inhibitor Combined with Trastuzumab in HER2-positive Breast Cancer - CHANG Jinyi; WANG Wei; CAI Haifeng (Zhongliu Fangzhi Yanjiu, 2022)
HER2 gene is expressed in 20%-30% of breast cancer patients, and HER2 expression provides a new direction for treatment. However, breast cancer with positive HER2 still has a poor prognosis and is prone to recurrence and metastasis. Trastuzumab is a classic basic drug for anti-HER2 therapy. However, the problem of primary and acquired drug resistance of trastuzumab has attracted people's attention. Studies have found that the occurrence of insensitive and drug resistance mechanism is related to PD-L1 up-regulation on tumor cell surface. Therefore, a large number of studies on PD-1/PD-L1 inhibitor combined with trastuzumab were carried out to improve its sensitivity and drug resistance. This article reviews the preclinical and clinical studies on PD-1/PD-L1 inhibitors in breast cancer with positive HER2.